'If it comes from Juazeiro, it's blessed'! Liquid and solid attachment in systems of object itineraries of pilgrimages. Issue 5 (24th March 2019) - Santana, Jannsen; Botelho, Delane
ABSTRACT: Building on an interpretive approach, we employ the multi-sited ethnographic methods of 'following the thing' and 'following the people' to track the movements of consumers and objects during a Catholic pilgrimage in the Northeast region of Brazil. We find a system of object itineraries that exemplifies how pilgrims liquefy and solidify attachments to objects to relate to God and saints during movements between their home and the sacred site. We expand perceptions by showing how materiality and relevance to the self can be important even in liquidity. Our findings have implications to the understanding of consumption of the spiritual and liquid/solid attachment to sacred objects.